Capital structure and stock prices: Evidence from listed joint-stock companies in Vietnam Stock Exchange - Minh, Ngo Ngoc; Huy, Cao Hoang (International Journal of Psychosocial Rehabilitation, 2020)
This paper applied the generalized least square (GLS) method to examine the relationship between capital structure and stock price of 554 non-financial joint-stock firms listed in Vietnam Stock Exchange for the period 2013-2019. The empirical results show that capital structure negatively significant impacts on stock price. In turn, the stock price affects positively and significantly capital structure. This evidence indicates that the market timing, the signaling and the pecking order theories are suitable to explain the relationship between capital structure and stock price of listed joint- stock companies in Vietnam.